Sometimes the apple does fall far from the tree: a case study on automatic indexing precision errors in PubMed - Wilson, Paije (Journal of the Medical Library Association, 2025)
Objective: This case study identifies the presence and prevalence of precision indexing errors in a subset of automatically indexed MEDLINE records in PubMed (specifically, all MEDLINE records automatically indexed with the MeSH term Malus, the genus name for apple trees). In short, how well does automatic indexing compare [figurative] apples to [literal] apples?  Methods: 1,705 MEDLINE records automatically indexed with the MeSH term Malus underwent title/abstract and full text screening to determine whether they were correctly indexed (i.e., the records were about Malus, meaning they discussed the literal fruit or tree) or incorrectly indexed (i.e., they were not about Malus, meaning they did not discuss the literal fruit or tree). The context and type of indexing error were documented for each erroneously indexed record. Results: 135 (7.9%) records were incorrectly indexed with the MeSH term Malus. The most common indexing error was due to the word "apple" being used in similes, metaphors, and idioms (80, or 59.2%), with the next most common error being due to "apple" being present in a name or term (50, or 37%). Additional indexing errors were attributed to the use of "apple" in acronyms, and, in one case, a reference to Sir Isaac Newton. Conclusion: As indicated by this study's findings, automatic indexing can commit errors when indexing records that have words with non-literal or alternative meanings in their titles or abstracts. Librarians should be mindful of the existence of automatic indexing errors, and instruct authors on how best to ameliorate the effects of them within their own manuscripts.